Energy flexibility as an example for a complex data exchange system = Elastyczność energetyczna jako przykład złożonego systemu wymiany danych - Krysik, Miłosz; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The increase of Renewable Energy Sources (RES) in the energy grid is crucial for the energy transition. Their proper integration and control allow achieving the strategic goals as well as coping with their dynamics by exploiting the flexibility available in energy system. This work presents the study on energy flexibility within the context of measurement and control, considering the relations between stakeholders and the Data Space approach.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne